Pre-Service Teacher & Mentor Clinical Experiences - Kevin L. Splichal (The Advocate, 2015)
Effective clinical experiences that pre-service teachers and pre-service teacher educators participate in are crucial for instruction to be highly effective and successful. However, the dynamics of different participating schools, mentors, instructors, and pre-service teachers add hundreds of variables to the quality of those experiences. How preservice teachers and mentors perceive those clinical experiences can help unravel those variables and provide ways to increase quality. Based on the research, one key question is foremost as a priority, namely, what are the characteristics of pre-service teacher and the mentor relationships? Further, do those relationships equate to effective clinical experiences for preservice teachers?